FORMATION OF ECOLOGICAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS BY MEANS OF ENVIRONMENTAL PROTECTION - Stakhova, Inna; Groshovenko, Olga; Pakhalchuk, Natalia; Zhovnych, Olesia; Komarivska, Nadiia; Bilyk, Tetiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The ecological crisis on a global scale (melting glaciers, explosions at nuclear power plants, pollution of rivers, seas, deforestation, harmful emissions into the atmosphere) requires radical changes in the process of its elimination. Volitional actions related to the cleansing, restoration and preservation of the natural environment are not enough, much emphasis is placed on educating a humane, environmentally conscious population capable of establishing harmonious relations with the natural environment. That is why higher education institutions face an important task – to form the environmental competence of future primary school teachers, to prepare students for the organization of environmental activities in working with younger students as a basis for shaping their environmental worldview. The article analyzes the theoretical foundations of the formation of environmental competence of future teachers, focuses on important summits, meetings, conferences, which rapidly and purposefully promote the preservation of the natural environment, stimulate the education of environmentally conscious younger generation. The aim of the article is to conduct an experimental study and establish the levels of formation of environmental competence of future teachers, based on its results to identify a model of formation of environmental competence of future teachers of higher education. In the course of the research we have singled out the main components (motivational, cognitive, activity, reflexive) of the formation of ecological competence of future teachers, as well as the corresponding criteria and levels. We conducted an experimental study to establish the level of environmental competence of future teachers among the leading pedagogical institutions of Ukraine: Vinnytsia Mykhailo Kotsiubynskyi State Pedagogical University, Kamianets-Podilskyi National Ivan Ohiienko University and T.N. Shevchenko National University "Chernihiv Colehium". The study made it possible to complete the model of formation of environmental competence of future primary school teachers by means of environmental activities (stages of implementation, priorities, pedagogical conditions, tools, forms). The study outlined new areas for further work.